Analisis Module Ajar Bahasa Inggris Di SMAN 15 Pekanbaru - Akbar Kurniawan; Fitri Wulandari (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
This research aims to analyze the teaching modules of PLP students in English subjects at SMA Negeri 15 Pekanbaru based on Minister of Education and Culture Regulation No. 22 of 2023. The two aspects analyzed are the completeness and systematic preparation of teaching module components and the suitability of the content based on Minister of Education and Culture Regulation No. 22 of 2023. This research uses a qualitative approach with descriptive methods. Data collection used document study techniques for teaching modules for PLP students in English subjects at SMA Negeri 15 Pekanbaru. Based on the descriptions above, it can be concluded as follows: (a) The teaching module developed by PLP students for English subjects at SMA Negeri 15 Pekanbaru has deficiencies in the completeness of the teaching module, namely in the learning material and there are differences in systematics. (b) The content of the teaching module was developed by PLP students in English subjects at SMA Negeri 15 Pekanbaru in accordance with the provisions of Minister of Education and Culture Regulation No. 22 of 2023